Neuroprotective Actions of Ghrelin and Growth Hormone Secretagogues - Frago, Laura M.; Baquedano, Eva; Argente, Jesús; Chowen, Julie A. (Frontiers in Molecular Neuroscience, 2011)
The brain incorporates and coordinates information based on the hormonal environment, receiving information from peripheral tissues through the circulation. Although it was initially thought that hormones only acted on the hypothalamus to perform endocrine functions, it is now known that they in fact exert diverse actions on many different brain regions including the hypothalamus. Ghrelin is a gastric hormone that stimulates growth hormone (GH) secretion and food intake to regulate energy homeostasis and body weight by binding to its receptor, GHS-R1a, which is most highly expressed in the pituitary and hypothalamus. In addition, ghrelin has effects on learning and memory, reward and motivation, anxiety and depression, and could be a potential therapeutic agent in neurodegenerative disorders where excitotoxic neuronal cell death and inflammatory processes are involved.